Internet of things (IoT) platform competition: consumer switching versus provider multihoming - Arturo Basaure; Alexandr Vesselkov (International Telecommunications Society (ITS), 2018)
Platforms that are understood as a place or system coordinating the interaction of different stakeholders (e.g., service consumers and providers) may enable widespread adoption of IoT services and applications. However, the lack of interoperability between platforms may inhibit the diffusion of IoT services by preventing reaching a critical mass and reducing competition as it makes consumer switching and service provider multihoming prohibitively expensive. Moreover, network effects inherent in multisided platforms may lead to a monopoly power in IoT market. This paper analyzes the effect of consumer switching costs and provider multihoming on market structure and competition by means of agent-based modelling. Simulation results suggest that service provider multihoming plays a key role in increasing market competition when switching costs decrease due to, for example, consumer data portability.
Keywords: 330; IoT; interoperability; network effect; data sharing; consumer switching; service provider multihoming; coopetition